2017
DOI: 10.1007/s11104-017-3374-y
|View full text |Cite
|
Sign up to set email alerts
|

Determining the fate of selenium in wheat biofortification: an isotopically labelled field trial study

Abstract: Aims The principal aim of this research was to quantify retention of a single, realistic Se biofortification application (10 g ha) in contrasting soils over two growing seasons utilizing an enriched stable Se isotope ( 77

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 41 publications
6
30
1
1
Order By: Relevance
“…This greater efficiency of foliar-applied fertilizers may be ascribed to (1) rapid uptake and assimilation due to application at a later growth stage, (2) less influence of root-to-shoot ratio on translocation to the edible parts of crops and (3) the avoidance of losses through fixation in soils. On average, only 12% of soil-applied Se fertilizers is taken up by plants; most Se applied is retained and immobilized in the soil 7 , with very little residual value for subsequent crops 17 . This means that repeated applications of Se fertilizers are required for each growth period, unless the efficacy of Se fertilizers can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…This greater efficiency of foliar-applied fertilizers may be ascribed to (1) rapid uptake and assimilation due to application at a later growth stage, (2) less influence of root-to-shoot ratio on translocation to the edible parts of crops and (3) the avoidance of losses through fixation in soils. On average, only 12% of soil-applied Se fertilizers is taken up by plants; most Se applied is retained and immobilized in the soil 7 , with very little residual value for subsequent crops 17 . This means that repeated applications of Se fertilizers are required for each growth period, unless the efficacy of Se fertilizers can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…A soil sequential fractionation procedure was adapted from Mathers et al (2017) and Shetaya et al (2012) to provide three fractions of Si, S, Se and I nominally identified as ‘Soluble’ (0.01 M KNO 3 ), ‘Adsorbed’ (0.016 M KH 2 PO 4 ) and ‘Organic’ (10% TMAH). Analysis was by ICP-MS (Thermo Fisher iCAP Q) in H 2 cell mode (Si and Se) or He cell mode with kinetic energy discrimination (I and S).…”
Section: Methodsmentioning
confidence: 99%
“…The spatial determination of minerals present in seeds can strengthen biofortification efforts, improve the understanding of the elemental redistribution during seed processing, steps such as grain polishing and crushing. Altogether, this can ensure that nutrients will reach the final consumer ( Gregory et al, 2017 ; Mathers et al, 2017 ; Zaman et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%